PENGARUH SOSIAL MEDIA MARKETING INSTAGRAM DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOPI JANJI JIWA - Hanif Rahman (2022)
Coffee is one of the commodities consumed by the people of Indonesia. The phenomenon that occurs under the name "Fever Coffee Shop" has an impact on the emergence of many coffee shops in Indonesia, both small and large scale. This research is a quantitative research with the aim of analysing and proving the influence of Social Media Marketing and Brand Image on the Purchase Decision of Kopi Janji Jiwa products. This study uses a population of consumers who have made a purchase at Kopi Janji Jiwa in East Jakarta. This study used 100 respondents who were selected through non-probability sampling and purposive sampling techniques. The data in this study were obtained from distributing questionnaires to be analysed using the Partial Least Square (PLS) method and assisted using the SmartPLS application. The results obtained from this research are: (1) Social Media Marketing Instagram variable has a positive and significant effect on the Purchase Decision variable with an Original Sample value of 0.633, (2) Brand Image Variable has a positive and significant effect on Purchase Decision variable with an Original Sample value of 0.301.